2017
DOI: 10.4037/ccn2017965
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Transfusing Blood Components in Patients With Trauma: A Conceptual Model

Abstract: Transfusion of blood components is often required in resuscitation of patients with major trauma. Packed red blood cells and platelets break down and undergo chemical changes during storage (known as the storage lesion) that lead to an inflammatory response once the blood components are transfused to patients. Although some evidence supports a detrimental association between transfusion and a patient’s outcome, the mechanisms connecting transfusion of stored components to outcomes remain unclear. The purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Although conceptually attractive, the relationship between WB use in trauma and its impact on patient outcomes has yet to be confirmed. Some evidence exists to support several benefits associated with the use of WB as compared with the use of CT in patients with major trauma (Bahr et al, 2019; Jones & Frazier, 2014, 2017). Investigators estimate that transfusion of CT in a 1:1:1 ratio results in a 38% loss of plasma coagulation factor concentration, 56% loss of platelets, and a 17% loss of red blood cells relative to WB (Jones & Frazier, 2014).…”
Section: Benefits To Patient Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although conceptually attractive, the relationship between WB use in trauma and its impact on patient outcomes has yet to be confirmed. Some evidence exists to support several benefits associated with the use of WB as compared with the use of CT in patients with major trauma (Bahr et al, 2019; Jones & Frazier, 2014, 2017). Investigators estimate that transfusion of CT in a 1:1:1 ratio results in a 38% loss of plasma coagulation factor concentration, 56% loss of platelets, and a 17% loss of red blood cells relative to WB (Jones & Frazier, 2014).…”
Section: Benefits To Patient Outcomesmentioning
confidence: 99%
“…Current data supporting improved outcomes associated with the use of WB in trauma are limited and complex. Between 2007 and 2019, only 12 studies have compared outcomes (e.g., 24-hr or in-hospital/30-day mortality, intensive care unit length of stay) between those who received WB and CT (see Table 1; Auten et al, 2015; Cotton et al, 2013; Ho & Leonard, 2011; Jones & Frazier, 2014, 2017; Keneally et al, 2015; Mays & Hess, 2017; Meyer et al, 2017; Nessen et al, 2013; Perkins et al, 2011; Seheult, Anto, et al, 2018; Seheult, Bahr, et al, 2018; Spinella et al, 2009; Thomas et al, 2019; Williams et al, 2020; Yazer et al, 2016; Zhu et al, 2019). Importantly, the definitions and types of WB used among institutions varied widely (see Table 2).…”
Section: Benefits To Patient Outcomesmentioning
confidence: 99%
“…Francischetti et al [10] found that post-cannulation platelet counts among other variables also have discriminative power within 30days in surviving patients on ECMO. Jones et al [11] claimed that packed platelets break down and undergo chemical changes during storage (known as the storage lesion) that lead to an inflammatory response once the blood components are transfused to patients deteriorating their outcome. Bruchim et al [12] significantly (P <0.05) associated the haemostatic derangements of lower tPCA at 12hours post presentation with the 60% mortality in dogs with naturally occurring heatstroke.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study focused on the effect of transfused RBCs, platelets and plasma are also associated with cellular and/or protein degradation during storage and increased risk of complications after trauma. 22 In addition, practitioners and blood banks may have selected specific-aged RBCs for massive transfusion. However, given the tempo of RBC transfusions in the PROPPR trial, we do not expect systematic bias.…”
Section: Limitationsmentioning
confidence: 99%